PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADAS PT. BANK SULUT (KANTOR PUSAT) - SRINLY PAAT; WILLIAM AREROS; TINNEKE TUMBEL (JURNAL ADMINISTRASI BISNIS, 2014)
To improve the performance of the employees, each company would require the human resource potential. Therefore various ways done by thecompany to determine the factors that cause an increase or decrease in EmployeePerformance. In this case, there are two factors that have been observed byresearchers, namely: leadership style and motivation. This study aims todetermine the effect of leadership style and motivation on employee performance.The data obtained in this study wa sthrough interviews with the company as wellas distributing questionnaires to 80 employees, and use a Correlation CoefficientAnalysis and Multiple Linear Regression. The results showed Leadership Styleand Motivation jointly influence on employee performance. However,in this studyMotivation is a major impact on employee performance compared withLeadership Styles.Keywords: Leadership Style, Motivation, Employee Performance.